2023
DOI: 10.1177/10748407221145963
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators Influencing Nurses’ Confidence in Managing Family Nursing Conversations in the Treatment of Chronic Noncancer Pain: A Longitudinal Qualitative Study

Abstract: This mixed-methods research examined the translation of a family nursing conversation intervention to the multidisciplinary treatment of patients experiencing chronic noncancer pain. The intervention required educating nurses who offered family nursing interventions to these families. The research uncovered barriers and facilitators influencing the nurses’ perceived self-efficacy related to the process of incorporating family nursing conversations in their nursing care. A qualitative, descriptive, longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Our FNC intervention represents a step toward that direction. Moreover, as nurses fulfill a prominent position to enhance a family-centered approaches (Berthelsen & Hølge-Hazelton, 2017; Dewing et al, 2021), they could be the appropriate professionals to deliver interventions aiming to pursue such a goal, even if they need to develop new competences (Rønne et al, 2023) and multidisciplinary collaboration is always encouraged (Stichler, 2015). Finally, our study showed that our intervention was feasible, but some aspects should be considered more carefully.…”
Section: Discussionmentioning
confidence: 99%
“…Our FNC intervention represents a step toward that direction. Moreover, as nurses fulfill a prominent position to enhance a family-centered approaches (Berthelsen & Hølge-Hazelton, 2017; Dewing et al, 2021), they could be the appropriate professionals to deliver interventions aiming to pursue such a goal, even if they need to develop new competences (Rønne et al, 2023) and multidisciplinary collaboration is always encouraged (Stichler, 2015). Finally, our study showed that our intervention was feasible, but some aspects should be considered more carefully.…”
Section: Discussionmentioning
confidence: 99%
“…What we do know is that it takes hours of experience and repeated rehearsals to become a competent intervening family nurse ( Bell, 2016 ; Shajani & Snell, 2019 ). A longitudinal qualitative FANCOC-PAIN study investigating the intervening nurses’ perspective illuminated an initial lack of confidence concerning their ability to meet the FNC intervention’s requirements ( Rønne, Esbensen, Brødsgaard, Rosenstrøm, et al, 2023 ). Eventually, the intervening nurses’ confidence increased, but the trial was conducted while they were still in a learning process.…”
Section: Discussionmentioning
confidence: 99%
“…The present trial was one study among three in the overall FANCOC-PAIN (FAmily Nursing COnversations Chronic non-cancer PAIN) study ( Rønne, Esbensen, Brødsgaard, Biering-Sørensen, et al, 2023 ; Rønne, Esbensen, Brødsgaard, Rosenstrøm, et al, 2023 ). The trial was registered on ClinicalTrials.gov (NCT03981302) and was thoroughly described in a protocol paper ( Rønne, Esbensen, et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Still, they were novices as facilitators of NLFCs, which was thoroughly discussed in the paper that reported the findings from the third FANCOC-PAIN study. 27 Since NLFCs takes hours to learn, 42 the participants’ experience of unfulfilled moments has to be interpreted within the picture of the nurses’ lack of experience. Furthermore, patients’ and family members’ views on nurses’ roles also seemed to affect their experience of unfulfilled moments.…”
Section: Discussionmentioning
confidence: 99%
“…A third FANCOC-PAIN study investigated the nurses’ process of acquiring the required skills. 27 Recruitment of patients and family members for the quasi-experimental trial’s control group took place between June and August 2019. The nurses’ education activities started in October 2019, and recruitment for the intervention group occurred between August 2020 and December 2021.…”
Section: Methodsmentioning
confidence: 99%